Upaya Perawat Dalam Fase Mitigasi Bencana Gunung Kelud Berdasarkan Icn Framework - agus khoirul anam (Jurnal Keperawatan Terapan, 2018)
Mental retardation is a condition of mental development that has stopped or is not complete. In most children's mental retardation, many problems can be to concern the parents. The objective of this research is to describe the attitude of parents in handling the mental retardation child in SDLB Negeri Bendo Kecamatan Kepanjenkidul, Blitar City. The design of the research is descriptive research. The population of the research is a whole of the parents of children with mental retardation who attended at SDLB Negeri Bendo Kecamatan Kepanjenkidul, Blitar City in academic year 2015-2016, a large sample of as much as 58 parents using technique of total sampling. The data collection was carried out by giving the questionnaire. The time of data retrieval is performed on 13 June until 13 July 2016. The results showed that of 55.2% or 32 parents who have a positive attitude in handling the child's mental retardation and 44.8% or 26 parents being negative attitude in the handling of child mental retardation. The factors that support it are age, number of children, and responsibility. The recommendations of this research are expected that the results of this research can provide input on the place of the research for involving parents in the treatment of mental retardation in a comprehensive manner.